Energy Analysis of Geothermal Resources in the Volcanic Zone of North Sumatra for Renewable and Reliable Power Supply - Roy Sianturi; Hendrik V. Sihombing; Janter Simanjuntak; Farel H. Napitupulu (Gio Vani Publisher, 2025)
Geothermal resources represent a vital component in Indonesia’s transition toward sustainable energy, particularly in volcanic regions such as the Sibayak field, North Sumatra. This study aims to evaluate the geothermal potential through integrated reservoir characterization, decline curve analysis, and Life Cycle Assessment (LCA). Field data from three exploration wells were analyzed, including temperature, pressure, enthalpy, and estimated capacity. Decline curve modeling was performed to assess production sustainability under scenarios with and without reinjection. Furthermore, LCA was applied to compare the environmental footprint of geothermal power with coal and natural gas. Results indicate reservoir temperatures ranging from 230–245 °C with enthalpy values exceeding 1,000 kJ/kg, supporting an estimated capacity of 50–55 MWe. Reinjection was shown to reduce annual production decline from 5% to 2%, thereby extending reservoir lifetime. LCA outcomes confirmed geothermal energy’s superior environmental performance, with CO₂ emissions as low as 90 g/kWh compared to coal (>1,000 g/kWh) and natural gas ( 450 g/kWh). These findings emphasize the strategic role of Sibayak geothermal development in strengthening Indonesia’s clean energy portfolio while ensuring long-term resource sustainability.